EMPOWERMENT OF FARMER GROUP THROUGH THE UTILIZATION OF PROCESSED CHAYOTE AS IMMUNE SYSTEMS - M. Sakung, Jamaludin; Pulukadang, Sri Hastuti Virgianti; Rahmawati, Sitti; Ahmar, Dewi Satria; Zikra, Muhammad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Chayote for farmer groups is currently only a commodity that is directly marketed, but with an abundance of production it makes farmers lose money due to lack of demand and difficult marketing places, so there is a need for innovation in suppressing the abundance of chayote production in preventing spoilage. This service aims to provide community understanding and skills in processing chayote plants into healthy food to improve the immune system. The methods of the activities carried out are: Counseling on the importance of diversification (diversification) of processed chayote products into biscuits made from chayote flour, to increase product added value, product shelf life and increase community income of chayote farmer groups. The results achieved from the training in making dodol and chayote-based brownies can improve the health and welfare of the people of Gumbasa sub-district, Sigi Regency, especially PKK women in Pandere village. The results of this service activity can increase community knowledge and skills, in mobilizing potential resources in the form of chayote owned by the community to increase income and community welfare based on technological innovation and local wisdom.